QoS routing in ad hoc wireless networks. - Chunhung Richard Lin (IEEE Journal on selected areas in communications)
The emergence of nomadic applications have generated much interest in wireless network infrastructures that support real-time communications. We propose a bandwidth routing protocol for quality-of-service (QoS) support in a multihop mobile network. The QoS routing feature is important for a mobile network to interconnect wired networks with QoS support (e.g., ATM, Internet, etc.). The QoS routing protocol can also work in a stand-alone multihop mobile network for real-time applications. This QoS routing protocol contains end-to-end bandwidth calculation and bandwidth allocation. Under such a routing protocol, the source (or the ATM gateway) is informed of the bandwidth and QoS available to any destination in the mobile network. This knowledge enables the establishment of QoS connections within the mobile network and the efficient support of real-time applications. In addition, it enables more efficient call admission control. In the case of ATM interconnection, the bandwidth information can be used to carry out intelligent handoff between ATM gateways and/or to extend the ATM virtual circuit (VC) service to the mobile network with possible renegotiation of QoS parameters at the gateway. We examine the system performance in various QoS traffic flows and mobility environments via simulation. Simulation results suggest distinct performance advantages of our protocol that calculates the bandwidth information. It is particularly useful in call admission control. Furthermore, ?standby? routing enhances the performance in the mobile environment. Simulation experiments show this improvement